Prediction of Static Recrystallization Nucleation Sites in Tensile Deformed Single Crystal Pure Iron through a Combination of In-Situ EBSD and CP-FEM - Zichao Luo (Metals, 2018)
Microstructure control is of vital importance in tailoring physical properties of metallic materials. Despite the enormous efforts devoted to the study of microstructure evolution during recrystallization, most previous research has been conducted under non-simple conditions, either applying complex deforming boundary conditions or employing specimens with sophisticated crystalline structure. These complexities hinder comprehensive understanding of the fundamental aspects in texture evolution and make it even harder to penetrate the already intricate recrystallization behaviors. The present study aims at a detailed evaluation of widely used phenomenological model in reproducing experimentally observed deformation characteristics under simple crystalline structure and deformation condition, as well as the prediction of nucleation sites during static recrystallization. In situ electron back-scattering diffusion (EBSD) observations were performed to record texture change during static recrystallization of single crystal pure iron specimens after tensile deformation. CP-FEM (crystal plasticity finite element method) method was employed to simulate deformed texture. Deformation heterogeneity characterized by kernel average misorientation maps derived from EBSD data and numerical calculations were compared. The former data shows deformation heterogeneity sensitive to localized microstrain while the later delivers an effective meso-scale deformation distribution. Observed approximate nucleation sites have shown a qualitative coincidence with highly distorted regions in numerical calculations.